Ameliorative potential of Adhatoda vasica against anti-tubercular drugs induced hepatic impairments in female Wistar rats in relation to oxidative stress and xeno-metabolism. (24th April 2021) - Sharma, Varsha; Kaur, Rajwinder; Sharma, Vijay Lakshmi
Abstract: Ethnopharmacological relevance: Adhatoda vasica Nees is widely used herb of indigenous system to treat various ailments especially upper respiratory tract infections. Not only, anti-tubercular efficacy of crude extract and phytoconstituents of A. vasica has been documented but its hepatoprotective role against various drugs mediated hepatic alterations in different animal models has also been observed. Background and purpose: Isoniazid, rifampicin and pyrazinamide (H-R-Z) are anti-tubercular drugs normally prescribed by health professionals for the treatment of tuberculosis, however along with their medical effectiveness these drugs also exhibit hepatotoxicity among TB patients. Unexpectedly, substantial toxicological data on the metabolism of anti-TB drugs are available but the mystery behind these xenobiotics is too complex and partly implicit. In this study, we further explored the hepatotoxic effects of these xeno-metabolic products and their amelioration by Adhatoda vasica Nees by elucidating its mechanistic action. Methods: We generated a hepatotoxic rodent model by oral administration of H, R and Z (30.85, 61.7 and 132.65 mg/kg body weight) drugs for 25 days in Wistar rats. Additionally, to achieve hepatoprotection two different doses of Adhatoda vasica Nees ethanolic leaf extract (200 and 300 mg/kg body weight) were used along with H-R-Z dosage, orally and once daily for 25 days and tried to ascertain their mechanistic action. For this, initially phytoconstituents of the extract were evaluated followed by extract standardization using RP-HPLC and FTIR methods. Furthermore, antioxidant activity of the extract was analyzed by DPPH assay. Finally, different treated groups were analyzed for hepatic oxidative stress markers, antioxidant markers, histopathological changes and gene expression study including CYP2E1, CYP7A1, NAT, NR1I2 and UGT1A1 genes involved in phase I and phase II xeno-metabolism. Results: Estimated content of vasicine in RP-HPLC method and free-radical scavenging activity in DPPH assay was found to be 134.519 ± 0.00269μg/10mg of leaf extract and 47.81 μg/mL respectively. In H-R-Z treated group, a significant increase in the levels of thiobarbituric acid, significant reduction in the levels of GSH, and enzymatic markers and marked changes in hepatic histological architecture were observed. In addition, there was significance up-regulation of CYP7A and NAT genes, down-regulation of CYP2E1 gene and insignificant expression levels of NR1I2 and UGT1A1 genes were observed in H-R-Z group. Conversely, high dose of A. vasica extract effectively diminished these alterations by declining oxidative stress and boosting of antioxidant levels. In addition, it acted as bi-functional inducer of both phase I ( CYP2E1 ) and phase II ( NAT and UGT1A1 ) enzyme systems. Conclusion: Hence, we concluded that anti-TB drugs exposure has potential to generate reactive metabolites that eventually cause hepatotoxicity by altering oxidant-antioxidant levels and their own metabolism. This study not only emphasized on xeno-metabolism mediated hepatic alterations but also explore the benefit of A. vasica on these toxic insults. Graphical abstract: Image 1